The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ejvs.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Simvastatin on NGAL, Matrix Metalloproteinases and Their Tissue Inhibitors in Human Intraluminal Thrombus and Abdominal Aortic Aneurysm Tissue

Abstract: Simvastatin treatment in patients with AAAs may influence the concentration of proteases and their inhibitors (TIMPs) in aneurysmal wall tissue and ILTs. Thus, further studies should be undertaken to understand the different influence of statin therapy on the components of the MMP/TIMP system in AAAs and ILTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…MAPK signaling pathway is a cellular pathway consisting of a large number of proteins that can be activated by a variety of extracellular stimuli. Activation of the MAPK pathway can result in a multitude of physiological effects, including apoptosis, cell proliferation, mitosis and the transcription of several classes of genes [20].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling pathway is a cellular pathway consisting of a large number of proteins that can be activated by a variety of extracellular stimuli. Activation of the MAPK pathway can result in a multitude of physiological effects, including apoptosis, cell proliferation, mitosis and the transcription of several classes of genes [20].…”
Section: Discussionmentioning
confidence: 99%
“…This study comprised 59 patients who underwent open AAA repair between September 2009 and December 2011 at the Department of Surgery, Medical University of Vienna, according to our previously described analysis [ 18 ]. We chose patients treated only with simvastatin or who had taken no statins for at least 6 months before the AAA repair and matched them by AAA diameter and age.…”
Section: Methodsmentioning
confidence: 99%
“…They improve endothelial cell function, modify inflammatory response, reduce VSMC proliferation, and attenuate cholesterol accumulation by reducing concentration of low-density lipoprotein (LDL), triglyceride-rich lipoproteins, and nonsteroidal isoprenoid compounds in plasma [ 15 17 ]. Our previous reports showed that patients treated with simvastatin had decreased oxidative stress, reduced proinflammatory TNF- α level, changed concentration of matrix metalloproteinase- (MMP-) 2, MMP-9, and tissue inhibitors of MMPs (TIMPs), and attenuated activity of proinflammatory mediators such as NF- κ B and extracellular signal regulated kinases (ERK) 1/2 [ 18 20 ]. Furthermore, statins target circulating neutrophil gelatinase-associated lipocalin (NGAL) and MMP-9/NGAL, the biomarkers of cardiovascular diseases [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…To verify the mechanism behind those changes, measurements were taken of the tissue levels of pro-inflammatory IL-6 and IL-17 and of anti-inflammatory IL-10, as well as the TLR4 receptor, which are known to regulate Cav-1 expression (Jones et al, 2001;Weiss et al, 2015). (Piechota-Polanczyk et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%